Akebia Saponin D inhibits the formation of atherosclerosis in ApoE−/− mice by attenuating oxidative stress-induced apoptosis in endothelial cells. (June 2019) - Yang, Song; Zhang, Wen; Xuan, Ling-ling; Han, Fei-fei; Lv, Ya-li; Wan, Zi-rui; Liu, He; Ren, Lu-lu; Gong, Li-li; Liu, Li-hong
Abstract: Background and aims: Akebia Saponin D (ASD) is a major bioactive triterpenoid saponin compound isolated from the Chinese herb Dipsacus asper wall (DSW). DSW has been long used as an anti-Alzheimer disease and anti-osteoporosis agent in clinics. However, anti-atherosclerotic effects of ASD have not been fully investigated. The objective of this study is to further investigate the anti-atherosclerotic activities and mechanisms of ASD in vivo and in vitro . Methods: In in vitro experiments, ASD (50, 100, and 200 μM) was used to explore the effects of preventing H2 O2 -induced endothelial cell apoptosis and the possible mechanism involved. In in vivo experiments, ApoE −/− mice were fed a high fat diet (HFD) and treated with atorvastatin (10 mg/kg/d), ASD (50, 150, 450 mg/kg/d), or the combination therapy (atorvastatin 10 mg/kg/d and ASD 150 mg/kg/d) for 14 weeks. Results: We found that ASD reduced the generation of reactive oxygen species, inhibited mitochondrial membrane potential (MMP) impairment, diminished the expression of Bax and Caspase-3, increased Bcl-2 expression, and inhibited apoptosis in endothelial cells. ASD significantly increased the expression of anti-oxidant enzymes (GSH, SOD, and CAT) in both liver and vascular tissue, reduced blood lipid levels (TG, TC, and LDL-C), and decreased lipid deposition in the liver and atherosclerotic lesion size in ApoE −/− mice. Conclusions: Our study revealed that ASD inhibited atherosclerosis development in ApoE −/− mice by inhibiting oxidative stress-induced endothelial cell apoptosis signaling pathway, and suggested that ASD might be a potential therapeutic drug in the prevention of atherosclerosis. Graphical abstract: Image 1 Highlights: Akebia Saponin D inhibits oxidative stress-induced apoptosis in human umbilical vein endothelial cells. Akebia Saponin D ameliorates lipid metabolism and inhibits lipid deposition in the liver and vascular tissue. Akebia Saponin D inhibits the formation of atherosclerotic plaque in ApoE −/− mice.